Long Term Culture of Mesenchymal Stem Cells: No Evidence of Chromosomal Instability - Zamani, Hamid; Karami, Fatemeh; Mehdizadeh, Mahshid; Baakhlag, Sedige; Zamani, Mehdi (Asian Pacific Journal of Cancer Biology, 2022)
Introduction: Mesenchymal stem cells (MSCs) technology has opened promising roads toward different aspects of medicine and biology. However, possible tumorgenic potential of MSCs has raised many concerns in using them in regenerative medicine. In the present study, we aimed to investigate the safety of MSCs by in-vitro culture and karyotype analysis. Materials and Methods: MSCs were successfully cultured in DMEM medium including 3.5 ng/ml recombinant human basic fibroblast growth factor (bFGF) and 20 % fetal bovine serum (FBS) within 25 passages. Results: No significant abnormality was observed in basic karyotype and morphology of MSCs in different passages of culture. Conclusions: Using of EGF free medium containing low bFGF concentration are possible explanations for observed integrity in karyotype and morphology of MSCs. Our findings would be further convincing evidence on the safety of MSCs under suggested conditions to guarantee using of them in regenerative medicine and disease treatment.